Progress in the Internationalization of the Educational Inspectorate of the Basque Country. STESSIE Project - Elósegui Ibarbia, Xabier; Ituarte Pérez, Maider (Avances en Supervisión Educativa, 2026)
This article aims to analyse the development and contributions of the European project STESSIE in the field of inclusive education, within the framework of the conference held in Madrid in 2025 on educational supervision and internationalization. It describes the collaboration among different European countries to design a digital tool intended to diagnose and assess the level of inclusion in educational institutions. The instrumentation is based on an application that collects data through questionnaires addressed to the educational community, while the procedure includes processes of self-evaluation, comparative analysis, and collaborative work among inspectorates and educational bodies. Furthermore, the lines of action focused on improving the tool, training professionals, and its international dissemination are outlined. As a result, the project highlights the value of reliable data in guiding inclusive educational policies, fostering continuous improvement in schools, and strengthening the role of inspection as a key agent in ensuring quality and equity in education.
Keywords: Information technology; Inclusive education; educational quality; exchange programmes; school supervision; European Union